Топологія поверхні тонких оксидних плівок CdO, сформованих на ван-дер-ваальсових поверхнях шаруватих кристалів InSe ТА GaSe - Кудринський, З.Р. (Физическая инженерия поверхности, 2013)
Методом магнетронного розпилення отримано тонкі плівки CdO на ван-дер-ваальсових поверхнях шаруватих кристалів InSe та GaSe. Структура плівок досліджена методом рентгеноструктурного аналізу. За допомогою атомно-силовоїмікроскопії проведено дослідження топології поверхні отриманих плівок. Встановлено, що їх поверхня є наноструктурованою, проте характер нарощування плівок на підкладках InSe та GaSe відрізняється. На InSe спостерігаються наноутворення у вигляді окремих пагорбів та їх скупчень. Густина таких наноутворень становить ∼2,25⋅10¹⁰ см⁻². Особливістю поверхневої топології плівок CdO на GaSe є те, що наноутворення розміщені рівномірно та мають куполоподібний вигляд, причому схильність до утворення скупчень у них відсутня. Оцінка густини такого типу наноутворень показує, що вона становить ∼6,4⋅10⁹ см⁻². Методом магнетронного распыления получены тонкие пленки CdO на ван-дер-ваальсовых поверхностях слоистых кристаллов InSe и GaSe. Структура пленок исследована методом рентгеноструктурного анализа. С помощью атомно-силовой микроскопии проведено исследование топологии поверхности полученных пленок. Установлено, что их поверхность является наноструктурированной, однако характер наращивания пленок на подложках InSe и GaSe отличается. На InSe наблюдаются нанообразования в виде отдельных холмов и их скоплений. Плотность таких нанообразований составляет ∼2,25⋅10¹⁰ см⁻². Особенностью поверхностной топологии пленок CdO на GaSe является то, что нанообразования размещены равномерно и имеют куполообразный вид, причем склонность к образованию скоплений у них отсутствует. Оценка плотности такого типа нанообразований показывает, что она составляет ∼6,4⋅10⁹ см⁻². Thin films of CdO were fabricated by dc reactive magnetron sputtering onto van der Waals surfaces of InSe and GaSe layered crystals. The structure of the films was studied by X-ray diffraction method. Surface topology of the obtained films was investigated by atomic force microscopy. It was established that the surface is nanostructured, but the growth of the films differs on InSe and GaSe substrates. On InSe substrate one can observe nanoobjects in the form of separate hills and their clusters. The density of such nanoobjects is ∼2,25⋅1010 cm–2. The peculiarity of surface topology of CdO films on GaSe is that the nanoobjects are distributed uniformly and have domelike shape. There is no tendency to formation of clusters of such nanoobjects. It was estimated that the density of these nanoobjects is ∼2,25⋅10¹⁰ cm⁻².Thin films of CdO were fabricated by dc reactive magnetron sputtering onto van der Waals surfaces of InSe and GaSe layered crystals. The structure of the films was studied by X-ray diffraction method. Surface topology of the obtained films was investigated by atomic force microscopy. It was established that the surface is nanostructured, but the growth of the films differs on InSe and GaSe substrates. On InSe substrate one can observe nanoobjects in the form of separate hills and their clusters. The density of such nanoobjects is ∼2,25⋅1010 cm–2. The peculiarity of surface topology of CdO films on GaSe is that the nanoobjects are distributed uniformly and have domelike shape. There is no tendency to formation of clusters of such nanoobjects. It was estimated that the density of these nanoobjects is ∼6,4⋅10⁹ cm⁻².